Combined Effects of Noise and Hand-transmitted Vibration on Workers’ Muscle and Mental Fatigues in a Simulated Construction Operation - Mousavi Kordmiri, Seyed Hojat; Aliabadi, Mohsen; Golmohammadi, Rostam; Bovenzi, Massimo; Farhadian, Maryam (La Medicina del Lavoro, 2023)
Background: The frequent use of hand-held vibrating tools by construction workers exposes them to hand-transmitted vibration (HTV) and noise. This study investigated the effect of combined exposure to HTV and noise on workers’ fatigues under simulated work with a typical building destruction tool. Methods:The repeated measures study was conducted on 40 construction workers exposed to HTV (5 m/s2 rms with frequencies of 31.5, 63, and 125 Hz), HTV (10 m/s2 rms- 31.5 Hz), noise (90 dBA), and concurrent exposure (noise (90 dBA) + HTV (10 m/s2 rms- 31.5 Hz)) with the typical vibrating hand-held tool for 30 minutes. Electromyography signals determined each worker’s fatigue level in the Flexor digitorum superficialis (FDS) muscle in two pre- and post-exposure periods. The subjects also filled out the visual analog scale to evaluate mental fatigue severity subjectively. Results:The mean difference of muscle fatigue parameters was significant in all scenarios except for the two scenarios of alone exposure to HTV (5 m/s2 -125 Hz and noise exposure (p-value < 0.05). The mean difference of mental fatigue in all scenarios except for the two scenarios of exposure to HTV (5 m/s2 -125 Hz) and exposure to HTV (5 m/s2 -63 Hz) was significant (p-value < 0.05). The most differences in muscle fatigue parameters (Amplitude = 8.16±5.63, Mean frequency=-4.69±3.78) and mental fatigue (4.97±2.38) were observed in the simultaneous exposure to noise and HTV. Conclusion: Noise exposure alone cannot produce remarkable effects on muscle fatigue but can aggravate the effects of vibrations as a consequence of synergistic interaction. However, the role of noise on perceived mental fatigue was more dominant than the HTV. These findings should be considered to adapt the existing exposure limits to actual work conditions.